The Concept of War: from History to Mythology (The Winners’ Feast by Aleksandr Solzhenitsyn and Maria’s Field by Oleg Bogayev) - Ищук-Фадеева, Нина И. (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article deals with the comparative analysis of two plays, The Winners’ Feast by Aleksandr Solzhenitsyn and Maria’s Field by Oleg Bogayev which, being united by the war theme, belong to different generations. More or less explicit implications present in both plays make it possible to view the Russian history as a form of national mythology.